2019
DOI: 10.1002/fsn3.1191
|View full text |Cite
|
Sign up to set email alerts
|

Coconut (Cocos nucifera L.) sap as a potential source of sugar: Antioxidant and nutritional properties

Abstract: This study was carried out to compare the antioxidant and nutritional properties of coconut (Cocos nucifera L.) sap with other natural sources of sugar such as sugar palm (Borassus flabellifer) and sugarcane (Saccharum officinarum L.). Coconut sap and juice from sugar palm and sugarcane were analyzed for proximate composition, pH and total soluble solid (TSS), color, sugar profile, vitamin profile, antioxidant properties (total phenolic contents, DPPH, FRAP, and ABTS), and mineral content. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 34 publications
2
45
2
1
Order By: Relevance
“…Martins & Van Boekel (2005) reported the formation of glycine–glucose adduct during the Maillard reaction. Sucrose, glucose and fructose were the primary sugars found in nipa sap (Phetrit et al ., 2020) and coconut sap (Asghar et al ., 2020c) as well as in sugar palm and sugarcane juices (Asghar et al ., 2020c). Upon heating and ultrasonic treatment, the reaction between the reducing sugars (glucose and fructose) presented in the nipa syrup and added glycine can produce the intermediate and glycated end products.…”
Section: Resultsmentioning
confidence: 99%
“…Martins & Van Boekel (2005) reported the formation of glycine–glucose adduct during the Maillard reaction. Sucrose, glucose and fructose were the primary sugars found in nipa sap (Phetrit et al ., 2020) and coconut sap (Asghar et al ., 2020c) as well as in sugar palm and sugarcane juices (Asghar et al ., 2020c). Upon heating and ultrasonic treatment, the reaction between the reducing sugars (glucose and fructose) presented in the nipa syrup and added glycine can produce the intermediate and glycated end products.…”
Section: Resultsmentioning
confidence: 99%
“…This mineral is also more represented in the raw material which is coconut sap with a higher content of 90.65 mg/100 mL according to the work of Okoma et al [6] Similarly, Asghar et al [7] found comparable amounts of potassium (96.08 mg/100mL) in the sap of coconut trees grown in Malaysia. Indeed, potassium is reported to be in high proportion in different parts of the coconut tree [8] .…”
Section: Discussionmentioning
confidence: 99%
“…The results of DPPH and ABTS were expressed as trolox equivalent antioxidant capacity (TEAC), which is µmol TEAC/g fresh weight and determined via a calibration curve, such as y = 0.7072x − 0.0081, R 2 = 0.9977 and y = 0.7021x − 0.0012, R 2 = 0.9985. The antioxidant activity was conducted using ferric reducing antioxidant power (FRAP) assay method, that is, under acidic conditions, the ability of antioxidants to reduce Fe 3+ ‐TPTZ (2,4,6‐tripyridyl‐s‐triazine) to produce blue Fe 2+ ‐TPTZ (Asghar et al., 2019; Oikeh et al., 2016; Razak et al., 2015). The absorbance was measured at 593 nm, and the FRAP results were represented as Fe (II) equivalent antioxidant capacity, which is µmol Fe (II)/g fresh weight, and determined via a standard curve (y = 1.2416x + 0.0134, R 2 = 0.9996).…”
Section: Methodsmentioning
confidence: 99%